2020
DOI: 10.15446/rfnam.v73n1.78824
|View full text |Cite
|
Sign up to set email alerts
|

Economic injury level and action thresholds for Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in maize crops

Abstract: Spodoptera frugiperda (J.E. Smith) is the pest insect that produces the highest losses in maize production in the tropics and neotropics. Its control in Colombia comprises about 10% of the total production costs. The aim of this study was to determine the economic injury level (EIL) and define action thresholds (ATs) for this insect pest in the maize hybrids 30F35R and 30F35HR (with Cry1F protein) in Espinal, Colombia. In two sowing cycles, a completely randomized design was established for each maize hybrid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…FAW infestation levels, as well as damage to maize plants, were significant at both sites. First, the overall average numbers of S. frugiperda larvae per plant obtained in our study (0.6–1.5 larvae across treatments and sites) are similar to those obtained by Adéyè et al [ 34 ] but higher than the action thresholds of 1.7–2.5 larvae per 10 plants established by Jaramillo-Barrios et al [ 50 ] in maize crops. Second, it has been reported that FAW infestations during the whorl stage may result in yield losses of up to 73% when 55 to 100% of the plants are infested [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…FAW infestation levels, as well as damage to maize plants, were significant at both sites. First, the overall average numbers of S. frugiperda larvae per plant obtained in our study (0.6–1.5 larvae across treatments and sites) are similar to those obtained by Adéyè et al [ 34 ] but higher than the action thresholds of 1.7–2.5 larvae per 10 plants established by Jaramillo-Barrios et al [ 50 ] in maize crops. Second, it has been reported that FAW infestations during the whorl stage may result in yield losses of up to 73% when 55 to 100% of the plants are infested [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…Control of fall armyworm and black cutworm with insecticide may be simultaneously reducing other early maize pests (Blanco et al 2014, Oliveira et al 2022). Insecticide seed coating and spray to prevent pest early damage can affect multiple pests (Harrison et al 1980, Evans and Stanly 1990, Marenco et al 1992, Wilde et al 2007, Jaramillo-Barrios et al 2020); therefore, the effect of reduction of herbivory by a single pest might be the effect of insecticides on multiple pests.…”
Section: Resultsmentioning
confidence: 99%
“…It then appeared in Caldas and Valle del Cauca, and then spread to all corn growing areas ( 30 ). Losses of up to 60% have been reported in Colombia due to S. frugiperda , which can increase production costs from 5.6 to 10.0% for technified corn ( 31 33 ). Blanco et al.…”
Section: Introductionmentioning
confidence: 99%
“…( 8 ), reported S. frugiperda to be the most damaging pest for non-Bt corn production in Colombia. Using chemicals to control S. frugiperda (organophosphates and pyrethroids) has become the most widely used method of reducing the impact of the insect in the field ( 33 ). These control measures have had a significant impact on the environment and the ability to resist S. frugiperda .…”
Section: Introductionmentioning
confidence: 99%